Electrochemical Immunosensor for the Sensitive Detection of Alzheimer's Biomarker Amyloid‐β (1–42) Using the Heme‐amyloid‐β (1–42) Complex as the Signal Source. Issue 2 (15th November 2021) - Ding, Minling; Shu, Qi; Zhang, Nan; Yan, Chaoren; Niu, Huizhe; Li, Xiaoqian; Guan, Ping; Hu, Xiaoling
Abstract: The amyloid‐β peptide (1–42) (Aβ42 ) can provide high diagnostic accuracy for the early diagnosis of Alzheimer's disease (AD). In this study, an immunosensor based on the peroxidase‐like activity of heme‐Aβ42 was designed for Aβ42 detection. The glassy carbon electrode (GCE) was electrodeposited Au particles (GCE/Au). The GCE/Au was modified using polythionine‐methylene blue (PTH−MB), AuNPs, monoclonal antibody (anti‐Aβ42 ), and bovine serum albumin (BSA), successively. The GCE/Au/PTH−MB/AuNPs/anti‐Aβ42 /BSA could competitively recognize Aβ42 and heme‐Aβ42 . The anchored heme‐Aβ42 showed strong electrocatalytic activity between H2 O2 and ferrocenemethanol. Under optimum conditions, we determined detection limits of 17.3 pM in PBS pH 7, 25.2 pM in serum, and 23.8 pM in saliva. The recovery ranged from 71.0 % to 117.8 %. Abstract :